Photoperiodic Regulation of Growth-Dormancy Cycling through Induction of Multiple Bud–Shoot Barriers Preventing Water Transport into the Winter Buds of Norway Spruce - Lee, YeonKyeong; Karunakaran, Chithra; Lahlali, Rachid; Liu, Xia; Tanino, Karen K.; Olsen, Jorunn E. (Frontiers in Plant Science, 2017)
Whereas long days (LD) sustain shoot elongation, short days (SD) induce growth cessation and formation of dormant buds in young individuals of a wide range of temperate and boreal tree species. In specific conifers, including Norway spruce, photoperiodic control of bud development is associated with the formation of a plate of thick-walled cells, denoted as the crown, at the base of the bud. Information about cellular characteristics of this crown region is limited. We aimed to test whether the crown region is an important SD-induced barrier ensuring dehydration of the developing winter bud by preventing water influx. Using microscopy and synchrotron techniques, we show here that under LD, cell walls in growing shoot tips had highly methyl-esterified homogalacturonan pectin. During SD-induced bud development, the homogalacturonan in the crown region was de-methyl-esterified, enabling Ca2+ binding and crosslinking, a process known to decrease cell wall water permeability by reducing pectin pore size. In addition, there was abundant callose deposition at plasmodesmata in the crown region, and xylem connections between the bud and the subtending shoot were blocked. Consistent with reduced water transport across the crown region into the bud, uptake of fluorescein in shoot tips was blocked at the base of the bud under SD. Upon transfer from SD to bud-break-inducing LD, these processes were reversed, and aquaporin transcript levels significantly increased in young stem tissue after 4 weeks under LD. These findings indicate that terminal bud development is associated with reduced water transport through decreased cell wall permeability and blocking of plasmodesmata and xylem connections in the crown structure. This provides further understanding of the regulatory mechanism for growth-dormancy cycling in coniferous tree species such as Norway spruce.